2018
DOI: 10.3390/f9040173
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Choosing Forest Stewardship Council (FSC) and Sustainable Green Ecosystem Council (SGEC) Schemes and the Effects of Certification Acquisition by Forestry Enterprises in Japan

Abstract: Abstract:The Forest Stewardship Council (FSC) and the Sustainable Green Ecosystem Council (SGEC) are deployed as forest certification schemes in Japan. This study aimed to identify the reasons that enterprises choose the FSC or the SGEC scheme and the effects of certification. A questionnaire survey was conducted on 126 forestry enterprises with certification as of May 2014. The results of questionnaire tabulation found different reasons for choosing FSC (high reliability of the international certification sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 16 publications
2
17
0
4
Order By: Relevance
“…The interviewed professionals suggested that forest certification has multiple effects that go beyond SFM of state forests. The same findings were found worldwide [8,10,26,27,29]. It is evident that instead of economic effects, FSC certification in selected SEE countries provides less measurable but equally important effects, such as improvements in public forest companies' image and better relations with customers, the general public and local communities.…”
Section: Professionals' Opinion On Implementation Of Fsc Fm Principlesupporting
confidence: 69%
See 1 more Smart Citation
“…The interviewed professionals suggested that forest certification has multiple effects that go beyond SFM of state forests. The same findings were found worldwide [8,10,26,27,29]. It is evident that instead of economic effects, FSC certification in selected SEE countries provides less measurable but equally important effects, such as improvements in public forest companies' image and better relations with customers, the general public and local communities.…”
Section: Professionals' Opinion On Implementation Of Fsc Fm Principlesupporting
confidence: 69%
“…Several studies analysed FSC's advantages and success or limitations and barriers [14][15][16][17], legitimacy [18], forest governance improvements [12,19,20], accountability [21], effectiveness [22], as well as consumers and private forest owners' perceptions and demands [7,[23][24][25]. Moreover, studies have also analysed the reasons why forest companies are changing their practices to comply with FSC standards [7] and investigated the reasons for selecting a particular forest certification scheme [26]. However, others have focused on the impacts of FSC forest certification on FM [27], business performance [9,20,[27][28][29][30][31] and ecosystem services [32][33][34] or studied the differences in FM practices between certified and non-certified forests [35].…”
Section: Introductionmentioning
confidence: 99%
“…A significant role in the sustainable development of forestry is played by the Forest Stewardship Council and the Sustainable Green Ecosystem Council through the proposed scheme of the international forest certification. Cooperation with such organizations should be increased to ensure reliable monitoring of forest use in countries around the world [2,3]. It is clear that the proposed certification scheme requires the usage of appropriate methodological accounting tools.…”
Section: Introductionmentioning
confidence: 99%
“…A universally-accepted scheme for sustainable forest management is forest certification, which has the potential to address certain environmental issues by establishing rules for sustainable management of forests, thus reducing the risks arising from environmental problems [1]. Previous studies on forest certification in Japan and Asia have indicated that the most common corrective action requests in terms of Forest Stewardship Council (FSC) principles or Sustainable Green Ecosystem Council (SGEC) standards are the following: management planning, environmental impact assessments, and monitoring [2][3][4][5][6][7][8][9][10]. Thus, mid-and long-term forest management planning is important for sustainable forest management.…”
Section: Introductionmentioning
confidence: 99%